Media literacy in responsive physical environments - Jacucci, Carlo (The University of Edinburgh, 2008)
This thesis addressed the production of media literacy practices in physical environments. It reflects a specific trajectory through a design space. The work is founded on four studies including design sessions and expositions in primary schools and in an art museum. The focus is on how to devise practices and make sense of media literacy tasks. the thesis addresses research problems of interaction design and media studies by:(a)configuring interactive tangibles and audiovisual media, to give different perspectives on media literacy within the same physical environment; (b) developing a set of practices which are attuned to how participants collaborate when accessing and producing media texts; (c) developing the design method by employing practical knowledge from theatre practices. The thesis tackles some specific design problems. One is that the qualities of the practices and qualities of the tools need to be addressed at the same time. Also, aesthetic and technical aspects often are indistinct. The thesis seeks help in some specific traditions in the performing arts. Some terms such as 'participatory theatre' and 'masked performance' are redefined in order to address both aspects of practices and tools. Terms such as 'gendre', 'framing', 'packaging', 'authoring', 'deconstruction', 'media agenda setting' are also redefined frm literature on media studies, through the production and study of collective activities. The thesis aims to contribute to the integration of findings in interaction desugb abd nedua stydues by (1) applying advances from interaction design for the support of new media literact practice in the physical environment; (2) applying the perspectives on media literacy which emerge from these integrations in order to contribute to current reesearch on interaction design. The thesis applies practices from the performing arts in order to enable a participatory design of physical environments for media literacy. The focus is on the role played by audience groups when they adopt media contents and artifacts.
Keywords: media literacy; physical environment